Simultaneous synthesis of a heat exchanger network with multiple utilities using utility substages. (4th August 2015) - Na, Jonggeol; Jung, Jaeheum; Park, Chansaem; Han, Chonghun
Highlights: Modified heat exchanger network synthesis is developed for considering multiple utilities. Concept of utility substages is implemented to superstructure. The novel mathematical model renders better solution for multiple utilities problems. Utility substage superstructure increases an effectiveness of searching solutions. Abstract: Heat exchanger network synthesis (HENS) has progressed by using mathematical programming-based simultaneous methodology. Although various considerations such as non-isothermal mixing and bypass streams are applied to consider real world alternatives in modeling phase, many challenges are faced because of its properties within non-convex mixed-integer nonlinear programming (MINLP). We propose a modified superstructure, which contains a utility substage for use in considering multiple utilities in a simultaneous MINLP model. To improve model size and convergence, fixed utility locations according to temperature and series connections between utilities are suggested. The numbers of constraints, discrete, and continuous variables show that overall model size decreases compared with previous research. Thus, it is possible to expand the feasible search area for reaching the nearest global solution. The model's effectiveness and applications are exemplified by several literature problems, where it is used to deduce a network superior to that of any other reported methodology.